Kesehatan Bank Sebagai Refleksi Kepercayaan Investor di Pasar Modal - Putri Indah Parawangsa; Kiryanto Kiryanto (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
From 2022 to 2024, issuers from the banking industry that are listed on the Indonesia Stock Exchange (IDX) will have their stock returns analysed to determine the effect of bank health, as defined by the CAMEL framework. Ratios of capital adequacy, non-performing loans, operating expenses to operating income, return on assets, and loan-to-deposit ratios are all part of the data set utilised in this analysis. Multiple linear regression analysis was used to provide a quantitative approach. The research sample consisted of 44 banking companies that were selected by purposive sampling. Secondary data collected from each company's annual report was utilised. In terms of their effects on stock returns, the study's authors found that ROA and LDR were positively predictive, whilst CAR, NPL, and BOPO were negatively predictive. On the other hand, at the 5% level of significance, none of these variables make a difference. At the same time, indices of bank soundness are shown to significantly impact stock returns. This suggests that external variables like macroeconomic conditions, monetary policy, and market sentiment have a larger impact on stock return swings than a bank's soundness does. Investors place a higher value on operational efficiency and profitability than other measures of a bank's health, according to these results. Consequently, investors are more influenced by a bank's profitability and operational efficiency when assessing the company's future prospects.